The timing of information updates: a stability result - Gomes, O. (2009)
We assume an environment where the current value of an aggregate nonstationary variable is generated by weighting the behavior of a large set of agents who choose to form expectations resorting to more or less outdated information concerning the state of the economy. Agents using recent information are able to produce expectations with a strong component of perfect foresight; agents resorting to outdated information will use predominantly the time series of the assumed variable to learn its long-term value. The main result is that a strong degree of information stickiness may imply a departure from stability (a Neimark-Sacker bifurcation occurs).